The Effects of Zakat, Infaq, Sadaqah, Social Aid, and Gross Regional Domestic Product per Capita on Income Inequality in Indonesia - Putri, Aura Permata; Herianingrum, Sri (Universitas Airlangga, 2025)
This study aimed to analyze the effect of ZIS (Zakat, Infaq, Alms), Social Assistance, and Gross Regional Domestic Product (GRDP) per capita on Income Inequality in 34 Provinces in Indonesia for the period of 2019-2023 partially and simultaneously. This research applied quantitative methods with multiple linear regression techniques. The data used in this study were secondary data on ZIS distribution from BAZNAS (National Amil Zakat Agency), realization of Social Assistance from KEMENKEU (Ministry of Finance), and Gross Regional Domestic Product (GRDP) per capita from BPS (Central Bureau of Statistics) in Indonesia for the 2019-2023 period. The results of the study showed that the distribution of ZIS funds (X1) has a negative and insignificant effect on the income inequality level. Social assistance realization has a negative and significant effect on income inequality. Gross Regional Domestic Product has a negative and significant effect on income inequality. ZIS, Social Assistance, and Gross Regional Domestic Product significantly affect income inequality in Indonesia from 2019 to 2023. This study suggested that zakat management institutions or agencies optimize ZIS funds to empower the mustahik economy and the entire community to increase literacy and awareness so that the collection and distribution of ZIS funds becomes optimal as a solution to the level of income inequality.